2016
DOI: 10.1016/j.ajhg.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Human Protective Modifiers: PLS3 and CORO1C Unravel Impaired Endocytosis in Spinal Muscular Atrophy and Rescue SMA Phenotype

Abstract: Homozygous loss of SMN1 causes spinal muscular atrophy (SMA), the most common and devastating childhood genetic motor-neuron disease. The copy gene SMN2 produces only ∼10% functional SMN protein, insufficient to counteract development of SMA. In contrast, the human genetic modifier plastin 3 (PLS3), an actin-binding and -bundling protein, fully protects against SMA in SMN1-deleted individuals carrying 3-4 SMN2 copies. Here, we demonstrate that the combinatorial effect of suboptimal SMN antisense oligonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
205
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(225 citation statements)
references
References 92 publications
13
205
0
Order By: Relevance
“…Consequently, SMN deficiency may impair targeting and local translation of axonal mRNAs essential for motor neuron development and maintenance 44, 45. Furthermore, SMN regulates several other fundamental cellular processes in the neuronal cytoplasm that are critical for maintaining axonal and synaptic health, including endocytic pathways, local translation, mitochondrial transport, and targeting to axons and ubiquitin homeostasis 46, 47, 48, 49, 50, 51…”
Section: How Low Levels Of Smn Cause Smamentioning
confidence: 99%
“…Consequently, SMN deficiency may impair targeting and local translation of axonal mRNAs essential for motor neuron development and maintenance 44, 45. Furthermore, SMN regulates several other fundamental cellular processes in the neuronal cytoplasm that are critical for maintaining axonal and synaptic health, including endocytic pathways, local translation, mitochondrial transport, and targeting to axons and ubiquitin homeostasis 46, 47, 48, 49, 50, 51…”
Section: How Low Levels Of Smn Cause Smamentioning
confidence: 99%
“…In agreement with this, PLS3 gene overexpression has been shown to refine axonal outgrowth in SMN-deficient MNs in a zebrafish model of SMA as well as in MNs cultured from mouse embryos [16,17]. Several studies have reported an actin-independent role of PLS3 in SMA modification [1,17]; however, investigations on the potential protective role of PLS3 against oxidative stress have not been performed.…”
Section: Introductionmentioning
confidence: 62%
“…In agreement with this, PLS3 gene overexpression has been shown to refine axonal outgrowth in SMN-deficient MNs in a zebrafish model of SMA as well as in MNs cultured from mouse embryos [16,17]. Several studies have reported an actin-independent role of PLS3 in SMA modification [1,17]; however, investigations on the potential protective role of PLS3 against oxidative stress have not been performed. Some reports have described the involvement of oxidative damage in the neurodegenerative process of SMA, and neuroprotection is considered to be an effective treatment option for many central nervous system disorders, including neurodegenerative diseases such as SMA [5,17].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations